Bluetooth low energy RF front-end for low-voltage applications in CMOS technology. - Silva, Roberto Rangel da (2019)
This work presents the analysis, design methodology and implementation of CMOS electronic circuits for operation in RF frequency, in the Industrial, Scientifical and Medical (ISM) band, following the Bluetooth Low Energy communication protocol, for the frequency band of 2.4 GHz to 2.4835 GHz. The contemporary motivation for working with Bluetooth, as well as the necessary performance parameters to be followed by the design is presented. Bluetooth Low Energy present a more flexible specification set, which helps with the reduction of supply voltage and power consumption. The considerations on how to work with MOSFETs with low voltage are presented, including the operation with inversion levels next to weak inversion region. Three implementations are presented, with results for LNA blocks and Front-End, which present a system with LNA and Mixer. The signal converted to an intermediate frequency is analyzed, as well as the LNA operation. All the presented design showed power consumption below 1 mW, for 0.5 V supply and linearity compatible with input power up to -20 dBm.